2011
DOI: 10.1155/2011/608041
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Long-Term Functional Results after Riboflavin UV A Corneal Cross-Linking

Abstract: Purpose. To report a comparative prospective long-term functional analysis after Riboflavin UV A corneal cross-linking (CXL) in three different age groups of patients affected by progressive keratoconus (KC). Methods. Functional analysis comprised paediatric patients (≤18 years) included 152 eyes (29.5%); intermediate group (19–26 years) 286 eyes (55.4%), and adults (≥27 years) 78 eyes (15.1%). CXL was performed according to the Siena protocol by using the Vega CBM (Caporossi-Baiocchi-Mazzotta) X linker (CSO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
2
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 23 publications
1
73
2
11
Order By: Relevance
“…8,9 Conventional epithelium-off crosslinking (CXL) demonstrated its safety and long-term efficacy in stabilizing progressive keratoconus and secondary ectasias in different clinical trials. [10][11][12][13][14] On the other hand, the procedure is time consuming, lasting from 40 min to 1 h. 15 The Bunsen-Roscoe's law of reciprocity [16][17][18] theoretically demonstrated that the photochemical process behind crosslinking depends on the absorbed UV-A energy and its biological effect is proportional to the total energy dose delivered in the tissue. [16][17][18] According to this concept, it is theoretically possible to deliver the same energy dose ensuring a proportional biological effect by setting different UV-A powers and exposure times in order to accelerate and shorten the crosslinking procedure in accelerated crosslinking (ACXL) modality.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Conventional epithelium-off crosslinking (CXL) demonstrated its safety and long-term efficacy in stabilizing progressive keratoconus and secondary ectasias in different clinical trials. [10][11][12][13][14] On the other hand, the procedure is time consuming, lasting from 40 min to 1 h. 15 The Bunsen-Roscoe's law of reciprocity [16][17][18] theoretically demonstrated that the photochemical process behind crosslinking depends on the absorbed UV-A energy and its biological effect is proportional to the total energy dose delivered in the tissue. [16][17][18] According to this concept, it is theoretically possible to deliver the same energy dose ensuring a proportional biological effect by setting different UV-A powers and exposure times in order to accelerate and shorten the crosslinking procedure in accelerated crosslinking (ACXL) modality.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the Siena CXL Pediatrics Trial also determined that the visual results were better in the pediatric age group, the difference compared to the adult age group was not significant. 22 In another study, the refractive results were found to be better in the adult age group. 6 Ulusoy et al reported that the increase in mean CDVA after accelerated corneal CXL in the pediatric group (<18 years) was 0.15 logMAR in patients with corneal thickness greater than 450 μm and 0.22 logMAR in patients with corneal thickness less than 450 μm.…”
Section: Discussionmentioning
confidence: 91%
“…In one study, in accelerated corneal CXL (9 mW/cm 2 ), a decrease of 2.04 D was detected in K max . On the other hand, in the Siena CXL Pediatrics Trial, the rate of reduction following conventional corneal CXL under protocol was found to be 0.7 D. 22,24 Ulusoy et al found a decrease of 1 D in mean keratometry in pediatric patients. 23 Similarly, variable results (0.06-0.8 D) were obtained in adult groups following accelerated corneal CXL.…”
Section: Discussionmentioning
confidence: 99%
“…Özellikle pediatrik yaş grubunda ilerleme daha hızlı olmakta ve hastalık başlangıcı bu yaş grubunda olan hastaların keratoplastiye gitme oranları daha fazladır. 10,11 Son yıllarda keratokonus tedavisinde yerini alan KÇB tedavisinin birçok çalışmada ilerlemeyi durdurduğu ve görmede artış sağladığı gösterilmiştir. 6,12,14 Caporossi ve ark.…”
Section: Discussionunclassified
“…6,12,14 Caporossi ve ark. 11 çalışmamıza benzer şekilde, KÇB yapılan olguları yaş gruplarına ayırarak bir çalışma yapmışlardır. Araştırmacılar, keratokonusta KÇB tedavisinin ilerlemenin daha hızlı olduğu özellikle pediatrik grupta ve ikinci olaraktan 26 yaş altı grupta etkili bulmuşlar ve KÇB'nin bu gruptaki hastalara uygulanacak ilk tedavi seçeneği olması gerektiği sonucuna varmışlardır.…”
Section: Discussionunclassified